PUBLIC POLICY ADMINISTRATION: CONCEPTUALIZATION OF THE CONCEPT IN MODERN CHALLENGES - Holub, Valeriya (Theory and Practice of Public Administration, 2019)
This article deals with the analysis of the basic approaches to the understanding of such concepts as “public policy and public administration” in modern challenges and also the background of institutionalization of new forms of government and civil society relations. It is determined that imperative to successful governance in new modernized countries is the formation of multilevel, multi-aspect and multifunctional system that is based on the corresponding structure of public policy administration. The formation of effective public policy, efficient system of its administration, conceptualization and definition of meaningful features of public policy administration in the context of rationalization of modern state functions and social development is the important part of the state development. The paper objective is to analyze of the process of institutionalization of new forms of government and civil society relations, increasing the dynamics of non-political actors’ participation according to the conceptualization of new areas of research - public policy administration. A feature of modern period of the state and society development is increasing of different actors’ influence on the processes of public policy formulation and implementation, growth of civic consciousness and activity, desire to influence the process in public policy and administration that occurs against the background of the strengthening of communication interactions and opening of information flows. Similar objective processes are the basis for the formation of new type of administration relations, changes in administration system as a whole, which is based on the structural and functional changes, which are founded on openness, coordination, responsibility, collegiality and cooperation of state and public institutions. Formation of a new type of integrated administration - public policy administration is going and its vector should be directed to the development of strategies and mechanisms of new institutional entities administrations. The basis of new forms of interaction should be organizational, structural and functional changes in accordance with the strengthened principles of coordination, cooperation and decentralization, which contributes to the formation of new system of public administration. New quality of public policy and public administration is connected to and is a consequence of social and political changes, institutionalization of new forms of government and civil society relations that promotes the formation of public policy administration system. The results actualized further researches in the context of improving the state functions and strengthening the subjectivity of civil society in transit states.